SARforMINE. A 2D/3D Web Service for the Underground Gas Storage Impact Monitoring - J. Blachowski; S. Biernat; D. Głąbicki; P. Grzempowski; A. Kaczmarek; K. Owczarz; B. Rosiak; A. Buczyńska (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Nowadays, satellite remote sensing produces vast amounts of Earth observation data, but without appropriate processing, visualization and interpretation, they are of limited use for a regular user. Web map applications are one of the approaches to share the data online. They allow not only for visualization, but also for analysis and interaction with geographic data. Such web services are used for a variety of purposes, fulfilling informational and educational roles. The SARforMINE is a geoportal service for monitoring, analysis and visualisations of predictive modelling of environmental impacts above underground gas storage facilities. The designed web map application represents information on selected environmental components, ground movements and vegetation condition derived from open-access satellite imagery, SAR and optical respectively. Additionally, historical data are analysed using machine learning for the purpose of predictive modelling of the potential future changes. The proposed approach outlines how web GIS services can augment traditional monitoring of underground gas storage sites.